Modified SMILE (mSMILE) and intensity-modulated radiotherapy (IMRT) for extranodal NK-T lymphoma nasal type in a single-center population. Issue 14 (5th December 2020) - Ghione, Paola; Qi, Shunan; Imber, Brandon S.; Seshan, Venkatraman; Moskowitz, Alison; Galasso, Natasha; Lunning, Matthew; Straus, David; Sauter, Craig; Dahi, Parastoo; Dogan, Ahmet; Yahalom, Joachim; et al.
Abstract: A modification of the SMILE regimen with dexamethasone, methotrexate, ifosfamide, L-asparaginase, etoposide (mSMILE) followed by Intensity-Modulated Radiotherapy (IMRT) at lower than usual dose, has been adopted as standard of care for extranodal NK-/T-cell lymphoma (ENKL) at our institution. mSMILE is a short course, intensive regimen incorporating pegylated asparaginase. Here, we describe clinical details, outcome and safety of patients receiving mSMILE. Among 28 patients with ENKL treated, response post-mSMILE was 93% (CR 68%), response post IMRT was 95% (CR 87.5%). Among early-stage patients/low PINK-E ( n  = 13), overall survival (OS) was 100% at the median follow-up of 31 months; progression-free survival (PFS) was 92%. Advanced-stage and intermediate/high PINK-E patients fared similarly (OS 43%, PFS 33.3% at the median follow-up). Thirty-two percent of the patients experienced G3-4 non-hematologic toxicity, all experienced hematologic toxicity. Most localized-stage patients achieved long-term disease control. Despite high response rates, most of the advanced stage patients relapsed quickly.